DEPTH DISTRIBUTION OF STRESSES IN THE HOKKAIDO WADATI-BENIOFF ZONE AS DEDUCED BY INVERSION OF EARTHQUAKE FOCAL MECHANISMS - Christova C.; Tsapanos T. (My University, 2000)
This study is based on the detailed geometry of the Hokkaido Wadati-Benioff zone and the paleosubduction zone as delineated by Hanus and Vanek (1984). The used data includes 217 CMT Harvard solutions for earthquakes, which belong to the Wadati-Benioff zone and 13 for the paleosubduction zone. The inverse technique by Gephart and Forsyth (1984) was incorporated for determining the best fit principal stress directions σ1,σ2,σ3 and the ratio (R=σ2-σ1/σ3-σ1) for 20 km depth intervals in the Wadati-Benioff zone and for the paleosubduction zone considered as a single body. In almost all the considered depth layers, the maximum compressive stress σ1 is normal to the strike of the slab and dips less than 25°, indicating the NW-SE convergence between the Pacific and Eurasian lithospheric plates. Exceptions are in the depth layer 81-120 km, the paleosubduction zone with steeply dipping along-strike σ1, and the lower part of the subduction zone (161-220 km) where σ1 is almost horizontal and of E trend. The minimum compressive stress σ3 is mostly along-strike and of a different dip with the exception of the 21-60 km layer wher they are down-dipping. The results obtained for the depth ranges 0-20 km, 81-100 km, 121-160 km, and the paleosubduction zone indicate heterogeneous stress fields. These results show that the slab pull and the mantle resistance, acting on the slab edge, are not the main forces which control the contemporary plate tectonics in the Hokkaido region. Along-strike compression at depths 81-120 km and along-strike extension at 0-20 and 61-220 km are involved in the slab dynamics. These can be related to horizontal bending of the subducting Pacific plate.